UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN SIRIH HUTAN (Piper aduncum L.) TERHADAP JAMUR Ganoderma boninense Pat. SECARA IN VITRO - Mahera, Ravika; Elfina, Yetti; Rustam, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to determine the ability of the wild betel leaf extract in inhibiting the grow thof fungi G.boninense.This reserach was conducted experimentally by using completely randomized design, which consists of 5 treatments and 4 replications, in each unit there were two petris dishes in order to obtain 40 units of treatment. The treatment being tested is the use of multiple concentrations of extracts of betel leaf meal ie 0, 25, 50, 75 and 100 g / l. Data were analyzed statistically using analysis of variance and furthertested withDuncan's Multiple Test New Multiple Range Test (DNMRT) at 5%. The results showed that the concentration of powder extract of wild betel significantly affected G. boninense and gave the different affected of fungi G. boninense. Powder extract of wild betel leaf at concentration 50 g/l water gave a better ability to control the fungus G. boninense namely 41,83 %. Â  Keyword : Stem root, G. boninense, P. aduncum, the concentration of leaf powder extract